Steel bridge decks : fatigue performance of joints between longitudinal stiffeners - 209392 Cuninghame, J. R.; Transport and Road Research Laboratory (Great Britain) (Crowthorne, Berkshire : Transport and Road Research Laboratory, 1982)
09